Análise de filmes antirreflexo de dióxido de titânio e nitreto de silício em células solares P+NN+ - Fagundes, Raquel Sanguiné (2012)
In this work we compared the antireflection coatings of titanium dioxide and silicon nitride for p+nn+ solar cell fabrication. This type of solar cell is more stable in the long term compared to n+pp+ cells and allows obtaining higher efficiencies. TiO2 films were produced by evaporation in high vacuum by electron beam and by chemical vapor deposition at atmospheric pressure (APCVD). The silicon nitride antireflection layer was obtained by reactive sputtering and by plasma enhanced chemical vapor deposition (PECVD). The films were deposited on textured silicon wafers and were characterized by measuring the spectral reflectance. Solar cells with these films were fabricated and characterized. The deposited films presented very low weighted reflectance, of around 1.8 % for silicon nitride films and 2.6 % for titanium dioxide ones, for any technique used. The lowest average weighted reflectance was obtained with SiNx:H thin films deposited by PECVD, with (1.93 ± 0.08) %. Concerning the homogeneity of the films, silicon nitride films presented the lowest standard deviation in the average weighted reflectance, of around 4 % relative. A thermal process performed at 840 °C in a belt furnace modifies the average weighted reflectance of about 0.3 % to 0.6 % absolutes for silicon nitride and TiO2 films, respectively. The p+nn+ solar cells doped with boron and phosphorus and metallized by screen printing reached the highest efficiencies where manufactured by using silicon nitride antireflection coating deposited by PECVD. The maximum efficiency of 13.7 % and an average of (13.5 ± 0.2) %, were achievied mainly because they showed a short circuit current density of around 1 mA/cm2 above that from solar cells with the other films investigated in this work. This difference is attributed not only to a low reflectance but also to a better surface passivation of SiNx:H layer.